PERAWATAN SALURAN AKAR GIGI MOLAR ATAS DENGAN CROWN LENGTHENING DAN RESTORASI ONLEI CERAMOPOLIMER - Putri, Asri Riany (Interdental: Jurnal Kedokteran Gigi, 2019)
Teeth post root canal treatment (RCT) would be very brittle because it has lost moisture and most of the hard tissue, so they need a restoration. Ceramopolymer is one of the choosen material for posterior onlay restoration recently. A tooth with subgingival caries often pose problems. Non adequat restoration can cause secondary caries and a failed restoration. The aim of this case report is to demonstrate a succeed treatment of crown lengthening with ceramopolymer onlay as post RCT restoration on maxilla secondary molar with irreversible pulpitis. A 30-year-old female patient was referred for RCT on the maxillary right second molar with irreversible pulpitis. RCT, crown lengthening and indirect onlay had been performed. Teeth that have taken RCT needs an restoration and ceramopolymer is a material that can be chosen. Ceramopolymer is an indirect restoration filled with 73% micro-fine ceramic. It combines the advantages of composite and ceramics so it provides a highly strong but elastic restoration for posterior teeth. Surgical crown lengthening can be done to gain access to subgingival area and cleaning the caries site and also to give an adequat tooth preparation. Crown lengthening with ceramopolymer onlay as post RCT restoration on maxilla secondary molar showed a successful treatment outcome.